Clockwork prince - Clare, Cassandra (New York Margaret K. McElderry Books, 2015)
As the Council attempts to strip Charlotte of her power, sixteen-year-old orphaned shapechanger Tessa Gray works with the London Shadowhunters to find the Magister and destroy his clockwork army, learning the secret of her own identity while investigating his past
1
Keywords: 1800 - 1901; Demonology -- Juvenile fiction; Demonology; Identity (Philosophical concept); Identity (Philosophical concept) -- Juvenile fiction; Orphans -- Juvenile fiction; Orphans; Paranormal fiction; Paranormal fiction; Secret societies -- Juvenile fiction; Secret societies; Demonology -- Fiction; Identity -- Fiction; London (England) -- History -- 19th century -- Fiction; Orphans -- Fiction; Secret societies -- Fiction; Supernatural -- Fiction; England -- London; Great Britain -- History -- Victoria, 1837-1901 -- Juvenile fiction; Great Britain; London (England) -- History -- 19th century -- Juvenile fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction; Fiction; History; Juvenile works